Regulatory T cell epitope content in human antibodies decreases during maturation - Gutierrez, Andres H.; Terry, Frances E.; Rosenberg, Amy S.; Martin, William D.; De Groot, Anne S. (Frontiers in Immunology, 2025)
IntroductionAntibody maturation in the lymphoid follicle produces antibodies with improved binding affinity. This process requires iterative rounds of mutation and B cell expansion, supported by T cells that recognize epitopes presented on the B cell’s MHC-II. In this comprehensive antibody repertoire analysis, we find that established regulatory T cell epitopes (Tregitopes) decline in maturing antibody sequences as somatic hypermutation (SHM) increases, but potential T effector epitopes do not decline. A previous analysis of B cell receptor (BCR)-derived HLA-DR epitopes present in memory antibody repertoires from seven healthy human donors revealed a decrease in donor-specific epitope content with SHM. Moreover, T cell epitope depletion was associated with class-switching and long-term secretion of antibody into serum. Significant depletion of high-affinity germline-encoded epitopes in high SHM sequences was also observed, but the predicted phenotype of T cells responding to the BCR-derived epitopes (regulatory vs. effector) was not previously evaluated.MethodsIn this follow-on study, we screened a different set of four donor repertoires to investigate the dynamics of donor-specific HLA-DR T cell epitopes and three subsets of T cell epitope content: previously validated T cell epitopes recognized by thymus-derived Tregs (Tregitopes), potentially tolerated T cell epitopes, and potential effector T cell epitopes.ResultsOur results show that Tregitope content reduction is correlated with SHM, suggesting that Tregitopes are removed during maturation. Moreover, T cell epitopes that are likely to be tolerated or tolerogenic were also removed with SHM progression. In contrast, potential T effector epitope content increased with SHM. Tregitope depletion occurred in multiple V-gene pair combinations and was the most frequent T cell epitope change. Furthermore, Tregitope content in IgA and IgG sequences was lower and had greater negative correlation with SHM than IgM, indicating that Tregitope removal is likely associated with class-switching. Tregitope depletion was also associated with maturation to plasmablasts. In vitro, representative Tregitopes inhibited CD4+ T cell proliferation. Mutations introduced by SHM altered Tregitope HLA-DR binding affinities.DiscussionThe correlation of Tregitope depletion with increasing SHM implies that the activity of thymus-derived Treg cells in immune responses to antibodies is diminished with SHM, maturation, and isotype switching, supporting the generation of anti-idiotype responses.